2022
DOI: 10.32734/joa.v9i3.8608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dormancy Treatment on Germination of Arabica Coffee ( Coffea arabica L.)

Abstract: The germination process of arabica coffee bean takes a fairly longtime, due to semi-permeable skin against water. Dormancy treatment needs to improve germination rate of coffee beans before planting. The research was conducted at The Compost Centre of Agriculture Faculty, University of Sumatera Utara from July – September 2018 using a Randomized Complex Design (RCD) non-factorial with 5 treatments, i.e. P0 (Control), P1 (Stripping Bark Horn), P2 (Soaking in KNO3 0,5% 24 hours), P3 (Soaking in Sitokinin 1,5 ml/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…if given in excessive amounts will inhibit plant growth. In line with other research results [8] that the application of NPK fertiliser 2.25 g / seedling showed better growth in oil palm seedlings.…”
Section: Discussionsupporting
confidence: 91%
“…if given in excessive amounts will inhibit plant growth. In line with other research results [8] that the application of NPK fertiliser 2.25 g / seedling showed better growth in oil palm seedlings.…”
Section: Discussionsupporting
confidence: 91%
“…Linda and Mukarlina [22] reported that coconut water at a concentration of 20% enhanced the shoot's emergence and shoot growth. Sitorus et al [23] observed that the treatment of young coconut water enhanced the growth of dragon fruit cuttings. The analysis showed that the growing medium only had a significant effect on dry root weight and had no significant effect on other variables (Tables 1 and 3).…”
Section: The Effect Of Immersion Period On the Growth Of Tea Cuttingsmentioning
confidence: 99%
“…Hasil penelitian Samanhudi, et al (2021) menunjukkan bahwa rerata panjang akar sorgum varietas Numbu nyata lebih tinggi (13,86 cm) dibandingkan dengan varietas Kawali (9,13 cm) dan varietas Sweet (8,73 cm). Selanjutnya dari sisi bobot akar, berdasarkan hasil penelitian Munthe, et al (2013), varietas Numbu memiliki bobot akar yang nyata lebih tinggi (165,56 g) dibandingkan dengan varietas Kawali (100,44 g) dan varietas Sangkur (114,00 g). Kondisi perakaran varietas Numbu dengan panjang dan bobot akar yang nyata lebih tinggi dibandingkan dengan varietas Kawali menyebabkan varietas Numbu memiliki kapasitas infiltrasi yang nyata lebih tinggi dibandingkan dengan varietas Kawali.…”
Section: Hasil Dan Pembahasan Kurva Infiltrasi Dengan Model Horton Ha...unclassified